Efficacy of universal masking for source control and personal protection from simulated cough and exhaled aerosols in a room. Issue 8 (3rd August 2021) - Lindsley, William G.; Beezhold, Donald H.; Coyle, Jayme; Derk, Raymond C.; Blachere, Francoise M.; Boots, Theresa; Reynolds, Jeffrey S.; McKinney, Walter G.; Sinsel, Erik; Noti, John D.
Abstract: Face masks reduce the expulsion of respiratory aerosols produced during coughs and exhalations ("source control"). Factors such as the directions in which people are facing (orientation) and separation distance also affect aerosol dispersion. However, it is not clear how the combined effects of masking, orientation, and distance affect the exposure of individuals to respiratory aerosols in indoor spaces. We placed a respiratory aerosol simulator ("source") and a breathing simulator ("recipient") in a 3 m × 3 m chamber and measured aerosol concentrations for different combinations of masking, orientation, and separation distance. When the simulators were front-to-front during coughing, masks reduced the 15-min mean aerosol concentration at the recipient by 92% at 0.9 and 1.8 m separation. When the simulators were side-by-side, masks reduced the concentration by 81% at 0.9 m and 78% at 1.8 m. During breathing, masks reduced the aerosol concentration by 66% when front-to-front and 76% when side-by-side at 0.9 m. Similar results were seen at 1.8 m. When the simulators were unmasked, changing the orientations from front-to-front to side-by-side reduced the cough aerosol concentration by 59% at 0.9 m and 60% at 1.8 m. When both simulators were masked, changing the orientations did not significantly change the concentration at either distance during coughing or breathing. Increasing the distance between the simulators from 0.9 m to 1.8 m during coughing reduced the aerosol concentration by 25% when no masks were worn but had little effect when both simulators were masked. During breathing, when neither simulator was masked, increasing the separation reduced the concentration by 13%, which approached significance, while the change was not significant when both source and recipient were masked. Our results show that universal masking reduces exposure to respiratory aerosol particles regardless of the orientation and separation distance between the source and recipient.